PAIN MANAGEMENT WITH A COMBINATION OF BACK MASSAGE THERAPY AND SLOW BREATH EXERCISE IN PAIN FOR ELDERLY RHEUMATOID ARTHRITIS PATIENTS - Lisdahayati, Lisdahayati; Pome, Gunardi; Saprianto, Saprianto; Martadinata, Umar Hasan; Adyatma, Adam Emha (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Pain in the elderly with Rheumatoid Arthritis is a significant health problem, affecting physical, psychological and social quality of life. Non-pharmacological therapies such as back massage and slow breath exercise are considered effective in reducing pain and increasing patient comfort. This study aims to evaluate the effectiveness of a combination of back massage therapy and slow breath exercise in pain management in elderly with Rheumatoid Arthritis. This study used a case study design with two elderly Rheumatoid Arthritis patients who experienced moderate pain. The intervention was carried out for three consecutive days, with a duration of 10-15 minutes per session. Data were collected through interviews, observations, and pain scale measurements using MNEMONIC PQRST. Data analysis was done descriptively. The results showed a significant decrease in the pain scale after the intervention. Client I experienced a decrease in pain from scale 5 (moderate) to scale 1 (mild), while Client II from scale 5 to scale 2 (mild). This combination of therapies proved effective in reducing pain and increasing patient comfort. The combination of back massage therapy and slow breath exercise is effective in reducing pain in the elderly with Rheumatoid Arthritis. This therapy can be recommended as a non-pharmacological intervention that is safe and easy to implement. Family support is needed in the application of this therapy to increase its effectiveness. Further research with a larger sample and longer duration of intervention is needed to corroborate these findings.